2022
DOI: 10.1126/sciadv.abm7814
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Shaker Kv channel and mechanism of slow C-type inactivation

Abstract: Voltage-activated potassium (Kv) channels open upon membrane depolarization and proceed to spontaneously inactivate. Inactivation controls neuronal firing rates and serves as a form of short-term memory and is implicated in various human neurological disorders. Here, we use high-resolution cryo–electron microscopy and computer simulations to determine one of the molecular mechanisms underlying this physiologically crucial process. Structures of the activated Shaker Kv channel and of its W434F mutant in lipid b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
65
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 98 publications
10
65
1
Order By: Relevance
“…Sodium conduction across the C-type inactivated state has been experimentally observed in hERG and also in the voltage-gated Shaker channel. 42 Furthermore, in recent experimental structures of a fast inactivating mutant of Shaker, both by cryo-EM 43 and by X-ray crystallography, 44 the SF appeared with binding sites S3 and S4 perfectly intact but with S1 and S2 sites enlarged compared to the canonical structure ( Figure 4 b). Thus, inactivation of Shaker seems to imply a widening of the extracellular portion of the SF rather than a constriction of its central region, as observed in the KcsA channel.…”
Section: Discussionmentioning
confidence: 88%
“…Sodium conduction across the C-type inactivated state has been experimentally observed in hERG and also in the voltage-gated Shaker channel. 42 Furthermore, in recent experimental structures of a fast inactivating mutant of Shaker, both by cryo-EM 43 and by X-ray crystallography, 44 the SF appeared with binding sites S3 and S4 perfectly intact but with S1 and S2 sites enlarged compared to the canonical structure ( Figure 4 b). Thus, inactivation of Shaker seems to imply a widening of the extracellular portion of the SF rather than a constriction of its central region, as observed in the KcsA channel.…”
Section: Discussionmentioning
confidence: 88%
“…High-resolution cryoEM and computer simulations have revealed additional dilated SF structures of the activated and C-type inactivated Shaker Kv channel and its W434 mutant in lipid bilayers 53 . A recent study reported structures of Kv1.3 channels that showed a dynamic selectivity filter with two discernable dilated conformations 54 , the authors hypothesizing that these may correspond to partially inactivated and inactivated states of the channel.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the selectivity filter of the K + channel KcsA adopts conductive or collapsed conformations, depending on the concentration of K + ( 79 , 83 ). Ion selectivity filter conformational changes also underlie pH dependence and inactivation gating in certain K2P and Shaker potassium channels ( 84 , 85 ). The observations that the selectivity filter of MCU has the same conformation in all structures determined to date, including those with MICU1-MICU2 bound, suggest that the selectivity filter does not undergo large conformational changes.…”
Section: Discussionmentioning
confidence: 99%